UJI PENDAHULUAN DAUN TENEM Litsea cubeba (Lour.) Pers - Risa Supriningrum; Medi Hendra; Hendri Misak (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Litsea cubeba (Lour Pers.) has been used by the Dayak community Lundayeh and Kenyah, the village of Long Berang, District Mentarang, North Borneo, as drug . Leaves and bark used as medicine for diarrhea. Preliminary data concerning the characteristics and content of secondary metabolites has not been reported. This study aims to determine the organoleptic, macroscopic, microscopic characteristics and content of secondary metabolites tenem leaves. The results showed that the leaf tenem have organoleptic characteristics typical aromatic smell like citrus (lemon), taste slightly bitter, slightly spicy, chelates. Macroscopic characteristics in the form of a single leaf, lanceolate, elongated, tapered leaf tip, leaf base tapering, bone pinnate leaves, upper surface shiny, lower surface dull and slightly hairy, color light green to dark green. Microscopy test results showed fragments of sklereid, oil cell, stomata type of parasitic, non-glandular trichomes. Simplicia tenem leaf powder contains alkaloids, tannins and terpenoids. The ethanol extract of leaves tenem containing compounds, terpenoids, tannins, alkaloids